2018
DOI: 10.1182/blood-2018-99-116013
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Efficacy, Pharmacokinetic (PK) and Biomarker Analyses of BCL2 Inhibitor Venetoclax (Ven) Plus MDM2 Inhibitor Idasanutlin (idasa) in Patients (pts) with Relapsed or Refractory (R/R) AML: A Phase Ib, Non-Randomized, Open-Label Study

Abstract: Introduction Effective therapies for R/R AML remain limited. MEK or MDM2 inhibition can downregulate MCL1, overcoming resistance to BCL2 inhibition. Preclinical synergy was seen when combining BCL2 inhibitor Ven with MEK inhibitor cobimetinib (cobi) or MDM2 inhibitor idasa (Han et al. ASH 2016; Pan et al. Cancer Cell 2017), supporting clinical evaluation in AML. Preliminary data in a Phase Ib dose-escalation study (NCT02670044) evaluating Ven+cobi/idasa in R/R AML suggested both combinations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…43,44 The efficacy and safety of the combination of venetoclax and idasanutlin has been investigated in a phase 1 study, including 39 patients with heavily pretreated relapsed refractory AML. 52 Preliminary efficacy data have shown an overall response rate (ORR) of 46%, with mutations in IDH1/2, RUNX1, JAK2, MPL, and CALR associating with greater clinical benefit, and mutations in FLT3 and/or TP53 associating with primary and/or secondary refractoriness. 52 By targeting the same pathway, Padua et al showed that GDC-0973 (also known as cobimetinib), a direct MEK inhibitor, was able to disrupt the RAS/BCL-2 complex in AML progenitors, overcoming resistance to venetoclax in patient-derived samples of AML.…”
Section: Combination Strategies To Boost Venetoclax Activity and Overmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 The efficacy and safety of the combination of venetoclax and idasanutlin has been investigated in a phase 1 study, including 39 patients with heavily pretreated relapsed refractory AML. 52 Preliminary efficacy data have shown an overall response rate (ORR) of 46%, with mutations in IDH1/2, RUNX1, JAK2, MPL, and CALR associating with greater clinical benefit, and mutations in FLT3 and/or TP53 associating with primary and/or secondary refractoriness. 52 By targeting the same pathway, Padua et al showed that GDC-0973 (also known as cobimetinib), a direct MEK inhibitor, was able to disrupt the RAS/BCL-2 complex in AML progenitors, overcoming resistance to venetoclax in patient-derived samples of AML.…”
Section: Combination Strategies To Boost Venetoclax Activity and Overmentioning
confidence: 99%
“…52 Preliminary efficacy data have shown an overall response rate (ORR) of 46%, with mutations in IDH1/2, RUNX1, JAK2, MPL, and CALR associating with greater clinical benefit, and mutations in FLT3 and/or TP53 associating with primary and/or secondary refractoriness. 52 By targeting the same pathway, Padua et al showed that GDC-0973 (also known as cobimetinib), a direct MEK inhibitor, was able to disrupt the RAS/BCL-2 complex in AML progenitors, overcoming resistance to venetoclax in patient-derived samples of AML. 45 Han et al subsequently demonstrated that this combination specifically targeted leukemia progenitors that express high levels of BCL-2 and causes the suppression of cytokineinduced pERK and pS6 signaling pathways exerted by cobimetinib.…”
Section: Combination Strategies To Boost Venetoclax Activity and Overmentioning
confidence: 99%
“…MDM2 inhibition has been shown to promote MCL-1 degradation in preclinical AML models [151]. Early results from a phase Ib study combining idasanutlin with venetoclax in relapsed/refractory AML have shown a response rate of 35.9%, with manageable toxicity [152]. Further studies combining venetoclax with novel therapies such as gemtuzumab ozogamicin, enasidenib and liposomal cytarabine and daunorubicin are ongoing (Table 2).…”
Section: Promising Combination Strategies In Hematological Malignanciesmentioning
confidence: 99%
“…Idasanutlin is also being investigated in a Phase Ib/II trial for r/r adult AML in combination with venetoclax, a B cell lymphoma-2 (BCL-2) inhibitor (NCT02670044) based on synergistic effect in preclinical studies [72]. Early clinical data have shown the combination to be safe with an anti-leukemic effect of 50% and a CR/CRi/CRp rate of 29% at the recommended Phase II dose [73]. A review on the efficacy of Idasanutlin in AML was recently published [74].…”
Section: Mdm2 Antagonistsmentioning
confidence: 99%